Higher red cell distribution width (RDW) is associated with increased all-cause and cardiovascular mortality in patients with breast cancer: A retrospective analysis of NHANES data (1999-2018). - Xuan Liu; Hao Wu; Saiqian Zhang; Zhu Zhu; Chao Liu; Jinmin Cao (PLoS ONE, 2025)
Background The correlation between red cell distribution width (RDW) and mortality in breast cancer participants is not well-defined. This study investigates the association between RDW and both all-cause and cardiovascular mortality in the US population. Methods A retrospective cohort study was performed using data from 15,806 participants in the NHANES dataset. Multivariable Cox regression models were used to analyze demographic, socioeconomic, clinical, and laboratory factors, with adjustments for potential confounders. Restricted cubic spline (RCS) analysis was utilized to investigate the non-linear associations between RDW and mortality outcomes, and Kaplan-Meier (KM) survival curves were created to illustrate RDW's effect on survival rates. Subgroup analyses and time-dependent ROC curves were also utilized to further assess the predictive value of RDW across different time intervals and patient subgroups. Results Elevated RDW significantly correlates with a heightened risk of all-cause mortality (adjusted HR 2.13, 95% CI 1.42-3.20) and cardiovascular mortality (adjusted HR 3.94, 95% CI 1.71-9.09) compared to lower RDW in Model 3. The association remained consistent across subgroups, with no significant interaction effects (p > 0.05). The RCS analysis demonstrated a positive linear relationship between RDW and mortality outcomes. Additionally, Kaplan-Meier analysis indicated that individuals with elevated RDW levels exhibited significantly lower survival rates. Time-dependent ROC and AUC analyses demonstrated that RDW was a more robust predictor of short-term mortality, as evidenced by higher AUC values in the initial years following diagnosis. Conclusions Red cell distribution width (RDW) serves as an independent predictor of both all-cause and cardiovascular mortality in breast cancer patients, showing strong predictive power for outcomes in both the short and long term.